Efficiency of Non-Governmental Zakat Institutions In Nigeria : An Introduction of Data Envelopment Analysis - El-Yakub, Tijjani; Abdul Rahim, Ahmad Khilmy (gbseglobal, 2023)
This study aims to evaluate the effectiveness of Nigeria's non-governmental zakat organisations (NZIs) over five years from 2015 to 2019. Data Envelopment Analysis (DEA) was used to analyse the data, and the findings revealed that non-governmental zakat organisations had a mean technical efficiency of 74.3%. It also demonstrated that when finding the technical efficiency of non-governmental zakat organisations in Nigeria, scale inefficiency predominates over pure technical inefficiency effects. Finally, it suggests that technology needs more consideration to increase productivity